The impact of comprehensive public hospital reforms on the direct medical cost of inpatients with coronary heart disease - Liu, Liming; Xu, Yue; Yu, Jingfei; Man, Xiaowei; Jiang, Yan; Zhao, Liying; Cheng, Wei (Frontiers in Public Health, 2022)
Objectives: To curb the unreasonable growth of medical expenses and reduce the burden of medical treatment, Beijing launched two rounds of comprehensive reform of public hospitals. In the two reforms, the addition of drugs and consumables were canceled successively. This study compared the changes in the direct medical cost of inpatients with coronary heart disease (CHD) in the three stages of two comprehensive public hospital reforms in Beijing and provides data support for health reform policies. Setting: CHD diagnosis and treatment data were extracted from the Hospital Information System (HIS) system of 33 public hospitals. The total amount and composition of the direct medical expenses of CHD inpatients in the three stages were calculated. Interrupted time series analysis was used to study the instantaneous changes and trend changes in the three stages. Participants: The data were obtained from the HIS system of 33 public hospitals above the second level in Beijing. A total of 66,647 medical and diagnosis records and 24,371,139 charge detail records were included. Results: After the two reforms, the total cost for CHD inpatients with most clinical classifications and treatment methods decreased. The proportion of drug and consumable costs decreased significantly, whereas the proportion of medical consultation service costs increased. Drug-treated patients were mainly affected by the instantaneous reforms, percutaneous coronary intervention-treated patients were simultaneously affected by instantaneous and trending effects, and coronary artery bypass graft-treated patients were mainly affected by the reform trend. Conclusion: The overall change in the direct medical cost of CHD inpatients was consistent with the goal of the comprehensive medical reform of public hospitals in Beijing, which is, "total control and structural adjustment."